2019
DOI: 10.1002/ardp.201900180
|View full text |Cite
|
Sign up to set email alerts
|

Arginolipid: A membrane‐active antifungal agent and its synergistic potential to combat drug resistance in clinical Candida isolates

Abstract: Antifungal drug resistance exhibits a major clinical challenge for treating nosocomial fungal infections. To find a possible solution, we synthesized and studied the antifungal activities of three different arginolipids (Nα‐acyl‐arginine ethyl ester) against clinical drug‐resistant isolates of Candida. The most active arginolipid, oleoyl arginine ethyl ester (OAEE) consisting of a long unsaturated hydrophobic chain, was tested for its mode of action, which revealed that it altered ergosterol biosynthesis and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…It was observed that OAEE alone depolarizes and damages plasma membrane, which in turn may favor the antifungal activity of fluconazole and AMB. Moreover, complexation between OAEE and AMB may fluidize plasma membrane, enhancing AMB antifungal activity (Patil et al 2020).…”
Section: Amphotericin B Associated To Synthetic Substancesmentioning
confidence: 99%
“…It was observed that OAEE alone depolarizes and damages plasma membrane, which in turn may favor the antifungal activity of fluconazole and AMB. Moreover, complexation between OAEE and AMB may fluidize plasma membrane, enhancing AMB antifungal activity (Patil et al 2020).…”
Section: Amphotericin B Associated To Synthetic Substancesmentioning
confidence: 99%
“…In fact, PI is a DNA-staining dye which upon binding to double stranded nucleic acid gives a red fluorescence when excited by a 480 nm laser [31]. This membrane-impermeant dye is generally excluded from viable cells, unless their membrane integrity is compromised [32].…”
Section: Propidium Iodide (Pi) Dye Uptake Assaymentioning
confidence: 99%
“…Hence, intravenous amphotericin B (AmB) is often used to treat people for whom azole therapy has failed [ 12 , 13 , 14 ]. In managing fungal life-threatening fungal infections, amphotericin B, a polyene antifungal antibiotic, has become the “gold standard” [ 15 ]. Regrettably, it is well known that long-term administration of AmB has been associated with severe renal toxicity.…”
Section: Introductionmentioning
confidence: 99%